1997
DOI: 10.1128/mcb.17.4.2326
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Interactions between the Vertebrate Polycomb-Group Protein BMI1 and Human Homologs of Polyhomeotic

Abstract: In Drosophila melanogaster, the Polycomb-group (PcG) genes have been identified as repressors of gene expression. They are part of a cellular memory system that is responsible for the stable transmission of gene activity to progeny cells. PcG proteins form a large multimeric, chromatin-associated protein complex, but the identity of its components is largely unknown. Here, we identify two human proteins, HPH1 and HPH2, that are associated with the vertebrate PcG protein BMI1. HPH1 and HPH2 coimmunoprecipitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
180
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(193 citation statements)
references
References 37 publications
12
180
1
Order By: Relevance
“…We found that the mouse homolog of the human Polyhomeotic protein, HPh2, interacts with dinG. Notably, previous studies have shown that Polyhomeotic proteins associate with Bmi-1 (Alkema et al, 1997a;Gunster et al, 1997). Our data further suggest that Bmi-1, dinG, and MPh2 associate to form a stable ternary complex in which each protein contributes to the binding of the others.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…We found that the mouse homolog of the human Polyhomeotic protein, HPh2, interacts with dinG. Notably, previous studies have shown that Polyhomeotic proteins associate with Bmi-1 (Alkema et al, 1997a;Gunster et al, 1997). Our data further suggest that Bmi-1, dinG, and MPh2 associate to form a stable ternary complex in which each protein contributes to the binding of the others.…”
Section: Introductionsupporting
confidence: 73%
“…Mammalian PcG genes have been identi®ed in mouse and in man and include bmi-1 and mel18, homologs of Drosophila Psc, and Su(2)Z; M33, HPc1, and HPc2, homologs of Drosophila Pc; Rae28/MPh1/ HPh1 and HPh2, homologs of Drosophila Ph; and eed, a Drosophila esc homolog (Tagawa et al, 1990;Haupt et al, 1991;van Lohuizen et al, 1991a,b;Pearce et al, 1992;Satijn et al, 1997;Alkema et al, 1997a;Gunster et al, 1997;Denisenko and Bomsztyk, 1997). The conserved function of these genes has been demonstrated by the homeotic transformation observed in bmi-1 and mel18 transgenic mice as well as by the ability of the mouse M33 gene to complement Pc mutations in Drosophila (van der Lugt et al, 1994;Alkema et al, 1995;Muller et al, 1995;Akasaka et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations